The Properties and Effects of Dust from Unpaved Roads on Vegetation and Microbes in the Karoo - Arendse, Lee-Roy (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScConsEcol)--Stellenbosch University, 2020.